Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
ta có \(S=\frac{6}{15}+\frac{6}{16}+\frac{6}{17}+\frac{6}{18}+\frac{6}{19}\)
\(\Rightarrow S>\frac{6}{20}+\frac{6}{20}+\frac{6}{20}+\frac{6}{20}+\frac{6}{20}\)
\(\Rightarrow S>\frac{30}{20}\)
\(\Rightarrow S>1.5>1\)
\(\Rightarrow s>1\)
Ta có :
\(S=\frac{6}{15}+\frac{6}{16}+\frac{6}{17}+\frac{6}{18}+\frac{6}{19}\)
\(\Rightarrow S< \frac{6}{15}+\frac{6}{15}+\frac{6}{15}+\frac{6}{15}+\frac{6}{15}\)
\(\Rightarrow S< \frac{30}{15}\)
\(\Rightarrow s< 2\)
Vậy \(1< S< 2\)
Ta có \(\dfrac{6}{15}>\dfrac{6}{16}>...>\dfrac{6}{19}\) nên \(S< \dfrac{6}{15}.5=2\).
Lại có \(S>\dfrac{6}{19}.5>1\) nên \(1< S< 2\)
Tìm số nguyên x, biết:
1) -16 + 23 + x = - 16
7+x=-16
x=-16-7
x=-23
2) 2x – 35 = 15
2x=15+35
2x=50
x=50:2
x=25
3) 3x + 17 = 12
3x=12-17
3x=-5
x=-5/3
4) (2x – 5) + 17 = 6
2x-5=6-17
2x-5=-11
2x=-11+5
2x=-6
x=-6:2
x=-3
5) 10 – 2(4 – 3x) = -4
2(4-3x)=10-(-4)
2(4-3x)=14
4-3x=14:2
4-3x=7
3x=4-7
3x=-3
x=-3:3
x=-1
6) - 12 + 3(-x + 7) = -18
3(-x+7)=-18-(-12)
3(x+7)=-6
x+7=-6:3
x+7=-2
x=-2-7
x=-9
1+2+3+4+5+6+7+8+9+10=55
11+12+13+14+15+16+17+18+19+20=155
1+2+3+4+5+6+7+8+9+10+11+12+13+14 +15+16+17+18+19+20+21+22+23+24+25+26+27+28+29+30-50-53=362
a ) CM : S < 1
Ta có :
6 /15> 6/30
6 /16> 6/30
6/17 > 6/30
6/18 > 6/30
6/19 > 6 / 30
=> S = 6/15 + 6/16 + 6/17 + 6/18 + 6/19 > 6/30 x 5 = 1
=> S > 1 ( 1 )
CM : S < 2
6/16 < 6/15 , 6/17 < 6/15 , 6/18 < 6/15 , 6/19 < 6/15
=> S = 6/15 + 6/16+ 6/17 + 6/18 + 6/19 < 6/15 x 5 = 2
=> S < 2 ( 2 )
Từ ( 1 ) , ( 2 ) => 1 < S < 2
b ) Do 1 < S < 2 => S ko phải STN
Chúc học giỏi !!!
\(S=\frac{6}{15}+\frac{6}{16}+\frac{6}{17}+\frac{6}{18}+\frac{6}{19}>\frac{6}{20}+\frac{6}{20}+\frac{6}{20}+\frac{6}{20}+\frac{6}{20}\)
\(S>\frac{6}{20}\cdot5=\frac{30}{20}\)
\(\Rightarrow S>\frac{3}{2}>1\)
\(S< \frac{6}{14}+\frac{6}{14}+\frac{6}{14}+\frac{6}{14}+\frac{6}{14}\)
\(S< \frac{6}{14}\cdot5=\frac{30}{14}\)
\(S< \frac{15}{7}\Rightarrow S< \frac{14}{7}+\frac{1}{7}\)
\(S< 2+\frac{1}{7}\)
\(\Rightarrow1< \frac{3}{2}< S< 2< 2+\frac{1}{7}\)
\(\Leftrightarrow1< S< 2\Rightarrow S\notin Z\)
a; A = -1 + 3 - 5 + 7 - 9 + 11 - 13 + 15 - 17
A = (-1 + 11) + ( 3 - 13) + (-5 + 15) + (7 - 17) - 9
A = 10 - 10 + 10 - 10 - 9
A = (10 - 10) + (10 - 10) - 9
A = 0 + 0 - 9
A = -9
b; B = 1+2-3-4+5+6-7-8+9+10-11-12+13+14-15-16+17+18-19-20
B = (1+2-3-4) + (5+6-7-8)+(9+10-11-12)+(13+14-15-16)+(17+18-19-20)
B= -4+(-4)+(-4)+(-4)+(-4)
B= -4 . 5
B= -20